2019
DOI: 10.1302/1863-2548.13.180174
|View full text |Cite
|
Sign up to set email alerts
|

Associations between risk factors and developmental dysplasia of the hip and ultrasonographic hip type: A retrospective case control study

Abstract: Purpose We aimed to revisit the correlation between the previously defined risk factors and the occurrence of developmental dysplasia of the hip (DDH) and to assess the influence of these factors on the ultrasonographic type of hip dysplasia according to the Graf’s classification in patients with DDH. Methods Data of healthy infants (mean age 33 days) who had bilateral mature (normal) hips (Graf type I) were compared with the data of infants (mean age 105 days) who were treated by abduction brace due to unilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 20 publications
1
38
2
Order By: Relevance
“…Kosar et al [22] reported that 5.6% of type IIa hips worsen sonographically at follow-up. Central nervous system anomalies, instability, and unilateral type IIa hips were predictors of worsening in their series [4]. This transition was more likely to occur in type IIa(−) patients according to the initial α angle measurements.…”
Section: The Effect Of Risk Factors On the Natural Course Of Graf Iiamentioning
confidence: 88%
See 2 more Smart Citations
“…Kosar et al [22] reported that 5.6% of type IIa hips worsen sonographically at follow-up. Central nervous system anomalies, instability, and unilateral type IIa hips were predictors of worsening in their series [4]. This transition was more likely to occur in type IIa(−) patients according to the initial α angle measurements.…”
Section: The Effect Of Risk Factors On the Natural Course Of Graf Iiamentioning
confidence: 88%
“…Although, the influence of various causative factors on the occurrence of DDH has widely been accepted, it is still not possible to put precisely one or more of these factors forward as the main cause(s) of DDH due to heterogeneity of the patient data and methodologies in different studies. Besides, to our knowledge, the correlation between the risk factors and the ultrasonographic types of hip pathology in patients [4]. Therefore, identifying the newborn infants with a higher risk of persistence or worsening of dysplasia is an important issue.…”
Section: The Effect Of Risk Factors On the Natural Course Of Graf Iiamentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1. presents these risk factors (genetic, epigenetic, mechanical and other) that include a number of areas that are not statistically significant but may be of clinical importance nevertheless [22]. Table 1.…”
Section: Epidemiologymentioning
confidence: 99%
“…There is a significant risk of DDH due to the high strain on lower extremities posed by the breech presentation [27], although breech babies are more likely to experience spontaneous resolution [22,28].…”
Section: Deliverymentioning
confidence: 99%